Holey Reduced Graphene Oxide Coupled with an Mo2N–Mo2C Heterojunction for Efficient Hydrogen Evolution. Issue 2 (22nd November 2017) - Yan, Haijing; Xie, Ying; Jiao, Yanqing; Wu, Aiping; Tian, Chungui; Zhang, Xiaomeng; Wang, Lei; Fu, Honggang
Abstract: An in situ catalytic etching strategy is developed to fabricate holey reduced graphene oxide along with simultaneous coupling with a small‐sized Mo2 N–Mo2 C heterojunction (Mo2 N–Mo2 C/HGr). The method includes the first immobilization of H3 PMo12 O40 (PMo12 ) clusters on graphite oxide (GO), followed by calcination in air and NH3 to form Mo2 N–Mo2 C/HGr. PMo12 not only acts as the Mo heterojunction source, but also provides the Mo species that can in situ catalyze the decomposition of adjacent reduced GO to form HGr, while the released gas (CO) and introduced NH3 simultaneously react with the Mo species to form an Mo2 N–Mo2 C heterojunction on HGr. The hybrid exhibits superior activity towards the hydrogen evolution reaction with low onset potentials of 11 mV (0.5m H2 SO4 ) and 18 mV (1m KOH) as well as remarkable stability. The activity in alkaline media is also superior to Pt/C at large current densities (>88 mA cm −2 ). The good activity of Mo2 N–Mo2 C/HGr is ascribed to its small size, the heterojunction of Mo2 N–Mo2 C, and the good charge/mass‐transfer ability of HGr, as supported by a series of experiments and theoretical calculations. Abstract : An in situ etching strategy is developed to fabricate holey reduced graphene oxide coupled to a small‐sized Mo2 N–Mo2 C heterojunction (Mo2 N–Mo2 C/HGr). Through the intimate contact of the Mo2 N and Mo2 C heterojunction and good charge‐/mass‐transfer ability of HGr, the hybrid benefits from its small size and exhibits superior electrocatalytic activity toward the hydrogen evolution reaction over a broad pH range.